Insecticide resistance monitoring in field populations of Chilo suppressalis Walker (Lepidoptera: Crambidae) from central China - Meng, Haoran; Huang, Rong; Wan, Hu; Li, Jianhong; Li, Junkai; Zhang, Xiaolei (Frontiers in Physiology, 2022)
Chilo suppressalis Walker (Lepidoptera: Crambidae) is a devastating rice crop pest in China. Chemical insecticides have been used to effectively managing C. suppressalis field populations in most of China’s agricultural regions. However, due to the intensive and extensive application of these insecticides, C. suppressalis has developed widespread resistance to many active ingredients. Thus, insecticide resistance development is a genuine concern for all crop specialists and growers. In this study, using the topical application method, we assessed the susceptibility of forty-six field populations of C. suppressalis to three insecticides in three Central Chinese provinces from 2010 to 2021. Our findings revealed that field populations of C. suppressalis built moderate to high levels of resistance to triazophos (Resistance Ratio (RR) = 41.9–250.0 folds), low to moderate levels of resistance to chlorpyrifos (RR = 9.5–95.2 folds), with the exception of the Zhijiang population in 2013 and the Xinyang population in 2015 at 4.8 folds and 3.4 folds resistance rates, respectively, despite showing susceptibility, and low and moderate levels of resistance to abamectin (RR = 4.1–53.5 folds). There were significant correlations between the activity of the detoxification enzymes (CarE) and the log LD50 values of triazophos. These results should help effective insecticide resistance management strategies reduce the risk of rapid build-ups of resistance to insecticides and slow down the process of selection for insecticide resistance.